I believe its 27 cause u have to multiply 3 times 3 which is 9, then 3 times 9 which is 27
Answer:
she is ether hiding something. or she just wants you to respect her privacy and she is trying to see how much you trust her so she can figure out how much she can trust you. i say you should just tell her you don't care what she does to just do what she would want and then let her actions decide whether she realy cares abought or respects yall's relationship. maby put it in kinder words than did tho or you might just pi22 her off
Step-by-step explanation:
the 22 is ss i just dont want to get banned
Answer:
(2, -5)
Step-by-step explanation:
x is defined by the first equation as x = -3y – 13. Substitute -3y – 13 for x in the second equation:
2( -3y – 13) + 2y = -6.
Performing the indicated multiplication, we get:
-6y - 26 + 2y = -6
Combining like terms results in:
-4y = 20, so that y = -5
Using the first equation, we find x for y = -5:
x = -3(-5) - 13 = 2
The solution is thus (2, -5) (Answer C)
A method that always works is to find the slope of the given line, then find the negative reciprocal of that. Your result will be the slope of the perpendicular line. Using this slope and the given point, fill in the parameters of the point-slope form of the equation of a line.
For m = slope of given line and (h, k) = given point, the perpendicular line will be
y = (-1/m)(x -h) +k
Often, this equation can be simplified to another appropriate form, such as slope-intercept form (y = mx+b) or standard form (ax+by=c).
_____
The slope of a given line can be found by solving its equation for y. The slope is the coefficient of x in that solution. If the given line is characterized by two points, (x1, y1) and (x2, y2), then its slope is m = (y2-y1)/(x2-x1).
In the unusual case where the given line is vertical (x=<some constant>), the slope of the perpendicular line is zero, and the line you want becomes y=k.
Answer:
Answer:x=
−3z−1
0
Step-by-step explanation:x=
Step 1: Add -2x to both sides.
2x+3z+4+−2x=2x+3+−2x
3z+4=3
Step 2: Add -3z to both sides.
3z+4+−3z=3+−3z
4=−3z+3
Step 3: Add -4 to both sides.
4+−4=−3z+3+−4
0=−3z−1
Step 4: Divide both sides by 0.
0
0
=
−3z−1
0
x=
−3z−1
0